Valoración de impactos generados por el cambio de uso del suelo en el Cantón Calvas, Loja - Cueva Cueva, Lilia Teresa (2024)
The main objective of this ongoing study was to established the impacts on the soil component generated by land use change in the Calvas canton between 1987 and 2022. Through the use of satellite images, which were processed with QGIS version 3.30.0 software, the land uses with the greatest impact on the environment was determined. Afterwards, the impacts were identified and assessed using the Conesa Importance matrix associated with the transformation occurring in a geographical area and over a period of time in the uses of agricultural, anthropic zone and other lands. Mainly, the change of forest areas transformed into agricultural, urban, and areas without vegetation cover was obtained. These changes unleash negative impacts such as loss of vegetation, increased urbanization, reduction of biodiversity, among others. These impacts are influenced by the topography of the piece of land. In order to counteract these several and critical impacts, an Environment Management Programme proposal was elaborated, which includes sustainable practices such as agroforestry and crop diversification, as well as innovative techniques such as hydroseeding, to rehabilitate the affected areas. This proposal could be useful as a reference for decision- makers in the planning of the territory in the Calvas canton.